Subversions of gender, sexuality and ageism: the play Oramortem by in-Próprio Coletivo (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
In this article, we analyzed how the categories of male and female are denaturalized in the play Oramortem (2015), which marks the emergence of in-Próprio Coletivo in the city of Cuiabá (MT). We sought to investigate how the assumption of a feminist discourse by the artist collective contradicted a historical trend in Brazilian theater and how it related to others distinct characteristics of that work such as the approach to sexuality of elderly people, the hybridism of artistic languages, the emphasis on visuality and the predominance of less substantial and affirmative modes of presence.
Keywords: Brazilian theater; contemporary theater; feminism; ageism